Competition, outside directors and executive turnover: Implications for corporate governance in the EU - Achim Buchwald (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
This study contributes to the ongoing debate on the relevance of non-executive outside directors for corporate governance building on a large panel of European listed firms in the period 2003 to 2011. Focusing on executive turnover as an indicator for effective monitoring, the findings reveal that outside directors and product market competition are substitutes. Outsiders increase the performance-turnover sensitivity of executives exclusively if competition in the industry is relatively weak. In an environment with effective competition, outsiders do not significantly influence the decision to replace underperforming managers. In fiercely competitive markets, the higher threat of bankruptcy or hostile takeover seems to effectively limit managerial discretion for opportunistic behavior.
Keywords: G34; J24; J63; L40; M00; 330; Competition; Corporate Governance; Executive Turnover; Outside Directors